Identification and aggressiveness of four isolates of Fusarium oxysporum f.sp. cubense from Latundan banana in Brazil. Issue 4 (22nd February 2017) - Araújo, Neilton Antonio Fiusa; Pasqual, Moacir; Pio, Leila Aparecida Salles; Alves, Eduardo; de Matos Moura, Nevenka; Costa, Sarah da Silva
Abstract: Members of Fusarium oxysporum species complex (FOSC) have been extensively studied because it causes many crop diseases and losses. This complex has more than 150 putatively plant host‐specific formae speciales such as F. oxysporum f.sp. cubense (Foc), the aetiological agent of Fusarium wilt of banana, Panama disease. The objective of this study was to characterize isolates obtained from rhizomes of the latundan (apple) variety of banana showing symptoms of Panama disease using morphological markers, phylogenetic analyses of the TEF ‐ 1 α and pathogenicity tests. Isolates were harvested from the states of Minas Gerais (Foc GO2), Goiás (Foc GO1 and Foc GO2A) and Bahia (Foc 807). Morphological markers of isolates observed are in accordance with the original descriptions of the F. oxysporum . Foc isolates grouped into two different lineages, and one of these is a lineage not yet recorded. Aggressiveness was assessed by a rating scale of the symptoms displayed in the shoot, rhizome and conducting vessels in latundan banana trees. The results indicated that all isolates belong to F. oxysporum f.sp. cubense, race 1. Isolate Foc GO2A proved to be more aggressive than the others. The results generated in this study contribute to knowledge of lineages diversity within Foc.